Paraneoplastic syndromes in rheumatology - Manger, Bernhard; Schett, Georg (Nature Reviews Rheumatology, 2014)
For patients that present with musculoskeletal symptoms, diagnostic procedures carried out by physicians and rheumatologists are primarily aimed at confirming or excluding the occurrence of primary rheumatic diseases. Another important trigger for musculoskeletal disease, however, is the presence of a tumour. Careful clinical investigation and knowledge of the gestalt of musculoskeletal syndromes related to respective tumour entities is of utmost importance for the diagnosis of paraneoplastic rheumatic diseases such as hypertrophic osteoarthropathy, paraneoplastic polyarthritis, RS3PE syndrome, palmar fasciitis and polyarthritis, cancer-associated myositis and tumour-induced osteomalacia. This places great responsibility on rheumatologists in diagnosing malignancies and referring the patient for effective treatment. The selective influence of tumours on musculoskeletal tissue is surprising and indicates that tumours alter tissues such as the periosteum, synovial membrane, subcutaneous connective tissue, fascia, muscles and bones by specific molecular processes. Some of the underlying mechanisms have been unravelled, providing valuable information on the physiologic and pathophysiologic roles of mediators such as vascular endothelial growth factor and fibroblast growth factor 23.
EVALuna2:12990